Board Composition and Underpricing : The Role of Business Experts, Support Specialists, Community Influentials, and Gender Diversity - Gupta, Lovleen; Maurya, Sheetal (Indian Journal of Finance, 2021)
The objective of this paper was to analyze the influence of resource, structural, and gender diversity on the boardroom of newly listed companies on IPO underpricing. To measure resource diversity, we categorized directors into support specialists, business experts, and community influentials and examined their influence on listing day demand for issue by investors. This study provided evidence in favor that directors with different skill sets, experience, and connections affected the IPO underpricing differently. Not all directors were equally influential; some of them, especially business experts and directors with political ties, were more influential than others. The findings noted an inverted U-shaped non-linear relationship of these directors with underpricing. This means that initially, the diversity affected the underpricing positively, and at a point of inflection, the relationship became negative. The results also indicated that the proportion of women directors had a statistically significant relation with underpricing. Overall, the present study confirmed the relevance of board diversity on demand for a public offering on listing day.